RELATIONSHIP OF INCENTIVES AND WORK ENVIRONMENT TO EMPLOYEES PERFORMANCE DURING THE COVID-19 PANDEMIC AT PT. ARTERI CIPTA RENCANA - David Havosan; Hotner Tampubolon; Fenny M. Hasugian (Fundamental Management Journal, 2022)
The purpose of this study was to analyze the relationship of incentives to the performance of employees of PT. Arteri Cipta Rencana as well as to analyze the relationship of the work environment to the performance of employees of PT. Artery Creation Plan. The research period used is from March 2022 to June 2022. The type of data used in this study is quantitative research using descriptive data processing methods consisting of Validity Test, Reliability Test, and Spearman Rank Test. The population in this study was 70 people, while for the sample, 41 people were taken using probability sampling technique. The data used in the form of employee biodata of PT. Arteri Cipta Rencana and questions consisting of 15 questions from each variable with a total of 45 questions. The results showed that all questions representing the three variables were valid and reliable. For hypothesis testing, it can be concluded that by using the spearman rank correlation test, it shows that there is a significant relationship between incentives and performance and there is also a significant relationship between work environment and performance. The author's suggestion from this research is that the company can pay more attention to the needs of employees such as providing incentives that are in accordance with performance and pay attention to the conditions of the work environment in order to remain in good condition. With these two conditions, employees can further improve their performance. Keyword: Incentives, Work Environment, Employee Performance